Fragility Analysis of Power Transmission Tower Subjected to Wind–Sand Loads - Xiaoqian Ma; Jun Lu; Benliang Li; Weiguang Tian; Yaxiao Zhang; Peng Zhang (Energies)
With the increasing construction of power transmission towers in desert regions for the transportation of wind or solar energy, structural safety under wind and sand loads has become critical. Current design codes primarily account for wind loads on these towers, overlooking the effects of sand impact. This study presents a new model to simulate sand–steel interactions and evaluates the fragility of transmission towers under both wind-only and combined wind–sand loads. The impact model is grounded in Hertz contact theory, with equations of motion derived for the interaction between wind-driven sand particles and structural members, solved via the central difference method. A parametric study investigates the effects of wind speed and sand particle mass: (1) impact forces and maximum deformations increase with wind speed, with impact duration initially decreasing up to 20 m/s and then gradually increasing; (2) an increase in sand particle mass leads to greater impact deformation, force, and duration. Fragility analysis, using incremental dynamic analysis, reveals that sand particles significantly amplify the tower’s response at high wind speeds and increase failure probability across all wind attack angles. These findings highlight the importance of incorporating sand-impact effects in the design and assessment of power transmission towers in desert environments to ensure structural safety and reliable operation of critical energy infrastructure.